THE EFFECTIVENESS OF USING THINK-TALK-WRITE (TTW) STRATEGY TO TEACH WRITING SKILL AT THE TENTH GRADE STUDENTS OF SMAN RAKSA BUDI - wijayati, eka; Seli, sastika; Triyogo, Agus (Lingustic, Literature and English Education, 2023)
The aim of the research was to find out the effectiveness of Think-Talk-Write (TTW) strategy at the tenth grade students of SMAN Raksa Budi. However the population and sample in this research were 32 Students (X IPA1) who were collected by using a purposive sampling technique. The research used a pre-exsperimental method. The pre-exsperimental class had given the treatments by using the Think-talk-write (TTW) strategy. The result shows as follow: first, the score point pre-test showed that the average score 55.6. After given the treatments the post-test was given. The score in the post-test result showed the average score was 75.87. However the result of the paired t-test taccount 12.6 while ttable 1.695. It means that the null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. In the order word, it can be announced that theThink-Talk-Write (TTW) Strategy were effective to used by students to write descriptive paragraphs. Therefore, it was significantly effective to use Think-Talk-Write (TTW) strategy to teach writing skill at the tenth grade students of SMAN Raksa Budi in academic year 2022/2023.